The occult in modernist art, literature, and cinema - Bauduin, Tessel M.,Johnsson, Henrik (Palgrave Macmillan, 2018)
Intro – Contents – Notes on Contributors – List of Figures – Chapter 1: Introduction: Conceptualizing Occult Modernism – Defining Occult Modernism – Untangling the Concept of Occult Modernism – The How and Why of Occultism – A Typology of Occult Modernism – Suggestions for Future Research – Investigations into Occult Modernism – Chapter 2: A History of Research into Occult Modernist Literature – First Generation: ca. 1940-1990 – Second Generation: ca. 1990-2000 – Third Generation: ca. 2000 to the Present – Concluding Remarks – Part I: Artistic Practices – Chapter 3: Visionary Mimesis and Occult Modernism in Literature and Art Around 1900 – The Limits of Postmodern Interpretations of Literary Visionary Mimesis – Maupassant and Meyrink: Realizing the Limits of Perception and the Exploration of 'New Senses' – Naturalist Clairvoyance as the Basis of August Strindberg's Visionary Mimesis – Symbolist Visionary Mimesis in the Works of Rainer Maria Rilke – Concluding Remarks – Chapter 4: August Strindberg's Art in Modernist and Occult Context – The Creative Process and the Unconscious Mind – Photographic Experiments 1: Celestographs and Crystallograms – Photographic Experiments 2: Photographing the Soul – Concluding Remarks – Chapter 5: 'Only Poets and Occultists Believe in Them Just Now': Fairies and the Modernist Crisis of Authorship – Fairies, Theosophy and Artistic Visions – Photographing the Invisible and Taking Dictation from the Fairies – Disenchantment, Fairy Art and the Many Shades of Belief – Splintering the Authorial Self, from Mallarmé to Yeats – The Fairy-Abducted Bard: Yeats's Experiments in Authorial Agency – Concluding Remarks – Part II: Aesthetics – Chapter 6: Return from Oblivion: Joséphin Péladan's Literary Esotericism – Introducing Péladan – An Early Modernist?.
Description based on publisher supplied metadata and other sources
Keywords: Religion; Religions; Secularism; Fine arts; Religious Studies; Occultism in art; Occultism in literature; Occultism in motion pictures; Electronic books